Strategy for eliminating high-frequency instability caused by multi-transmitting boundary in numerical simulation of seismic site effect - Yang, Yu; Li, Xiaojun; Rong, Mianshui; Yang, Zhibo (Frontiers in Earth Science, 2022)
A multi-transmitting boundary is a local artificial boundary widely used for numerically simulating seismic site effects. However, similar to other artificial boundaries, the multi-transmitting boundary is unstable in numerical simulation. Based on the concept of multi-directional transmitting formula, a measure for eliminating the high-frequency instability of the transmitting boundary is studied using a neighbour node of a boundary node to realize smoothing filtering. The proposed strategy is verified through numerical analysis. The smoothing coefficient chosen for this measure provides a reference for deriving the coefficient of multidirectional transmitting formula in the time domain.